Use of Volume/ Allometric Equations in National Biomass Estimation - Lakhchaura, Prakash (Indian Forester, 2016)
The role of volume/allometric equations in precise estimation of National Forest Biomass/Carbon is immense. In the United Nations Framework Convention on Climate Change, the potential benefits for non-annex-I parties will be based on results that must be measured, reported and verified. Therefore, precise volume/allometric equations will play an important role in verifying the volume and carbon stock estimates for the country. The data collected during National Forest Inventory (NFI) is used for estimation of carbon stock in country’s forest using species wise volume/allometric equations developed by FSI. FSI has developed around 750 volume equations for 190 species spread throughout India, Bhutan and parts of Nepal. In addition, FSI also developed more than 600 allometric biomass equations for different species in different physiographic zones of the country through a special study. FSI continuously develop local volume equations using the data collected during NFI and used them for estimation of volume. In addition, volume equation can be used for estimation of quantity of wood containin trees, prediction in future yield and estimation of increment.